ASTM F75 Alloys: A Systematic Review of Microstructural Characteristics and Manufacturing Advances from Conventional to Laser-Based Techniques with Bibliometric Analysis - Raghad Ahmed Al-Aloosi; Wisam T. Abbood; Enas A. Khalid; Wassan S. Abd Al-Sahb; Nazar Kais Al-Karkhi; Oday I. Abdullah; Somer Nacy; Adawiya J. Haider; M. N. Mohammed (Bumi Publikasi Nusantara, 2027)
This study provides a systematic and bibliometric review of ASTM F75 cobalt–chromium alloys, focusing on microstructure and the shift from conventional to laser-based manufacturing. Using combined analytical methods, it evaluates microstructure, mechanical properties, corrosion behavior, and biocompatibility. Results show that laser-based techniques such as LPBF and DMLS produce finer grain sizes (1–10 µm vs. 50–200 µm), leading to improved hardness (20–40%) and tensile strength (15–30%). Despite challenges like residual stress and process optimization, these methods show strong potential for high-performance and sustainable applications.